Lactobacillus Endocarditis-Associated Glomerulonephritis Complicated by anti-Coagulant Nephropathy and Renal Amyloidosis - Mitchell Moosavi; Jonathan E. Zuckerman (Case Reports in Pathology)
Kidney injury is a well-known sequelae of infectious endocarditis. Various types of kidney injury can be seen, including endocarditis-associated glomerulonephritis, and may affect nearly half of the patients with infectious endocarditis. Lactobacillus species are an infrequently documented cause of endocarditis. We present a case of Lactobacillus endocarditis-associated glomerulonephritis in a patient with a complex medical history including Lactobacillus infection of an artificial heart valve. To our knowledge, this is the first reported case of development of endocarditis-associated glomerulonephritis secondary to Lactobacillus species organisms. Furthermore, the patient’s renal biopsy revealed several frequently overlooked concomitant findings including anti-coagulant nephropathy and renal amyloidosis.